Key insights for teaching and learning in higher education - Rosli, D'oria Islamiah (Jabatan Pendidikan Tinggi, KPT, 2024)
Key Insights for Teaching and Learning in Higher Education serves as a foundational guide for new lecturers in Malaysia, emphasizing the essential competencies required for effective teaching in higher learning institutions. Covering areas such as academic accountability, curriculum design, teaching methods, and student assessment, the book highlights the importance of structured training, competent facilitators, and continuous professional development. It reinforces the need for institutions to integrate these elements into their academic development plans to cultivate respected, professional educators in higher education.